A versatile cellulose nanocrystal‑carbon dots architecture: Preparation and environmental/biological applications. (15th December 2022) - Li, Ruyi; Liang, Fangyuan; Hu, Xianyun; Bian, Huiyang; Deng, Chao; Seidi, Farzad; Zhang, Baiyang; Xiao, Huining; Liu, Yuqian
Abstract: In this work, a versatile cellulose nanocrystal‑carbon dots (CNC-CDs) architecture is prepared and applied in environmental remediation and biological sensing. The citric acid (CA) is employed to extract CNCs and in-situ synthesize blue-emissive CDs. The carboxyl-rich surface of CNC-CDs enables the chelation of Hg 2+ and fluorescence quenching of CDs, realizing the detection and adsorption of Hg 2+ with a film comprised of the architecture. The limit of detection (LOD) is measured as 12.8 nM with satisfying retention efficiency. The versatility of CNC-CDs is demonstrated by the fabrication of a fluorescence resonance energy transfer (FRET) sensor using m-tetrakis(4-sulfonatophenyl)porphine (TSPP) as FRET acceptor and Fe 3+ receptor. Fluorescence of the sensor is responsive to Fe 3+ in a ratiometric manner, which significantly contributes to the visualized and sensitive Fe 3+ detection (6.9 nM). In combination with excellent biocompatibility, the FRET sensor is capable of imaging intracellular Fe 3+ . Graphical abstract: Fluorescent CNC-CDs are fabricated by successive esterification‑carbonization, and shows excellent versatility in environmental and biomedical applications. Unlabelled Image